Investigation into the suitability of kinect sensor for automated body measurement - Ejidokun Temitayo; Adigun Samson Olasunkanmi; Olutayo-Irheren E. Olutayo; Rabbilfattah Ozovehe Yusuf (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Due to the low cost and wide availability of the Kinect sensor, researchers and experts in the field of anthropometry, sizing and clothing fiting are leveraging on its inbuilt 3D camera to develop systems for automated body measurement. This study focuses on the evaluation of the Microsoft Kinect (V1) sensor to determine its suitability for automated body measurement. The study was conducted by data collection of various body dimensions of test subjects using a measuring tape as a reference. Furthermore, a statistical approach known as the measurement system analysis was used to investigate the sensor's capability to produce accurate, reliable and consistent body measurements. The results obtained shows indicates that there exists very little variation when the measurement is repeated. Also, the instrument is relatively stable, with minimal bias which can be corrected by calibration. The outcome of the study proves the effectiveness of the Microsoft Kinect sensor as a means of conducting body measurement.